CIVIL SOCIETY COLLABORATION IN THE DEVELOPMENT OF ISLAM AND ITS IMPLICATIONS FOR RELIGIOUS HARMONY IN THE PHILIPPINES - Winengan; Muhammad Syaoki; Widiya Ayu Safitri (Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
Islam in the Philippines faces significant challenges but also holds immense potential for peaceful and productive development. The long history of conflict and struggle within the Muslim community highlights the importance of adaptive and context-sensitive da'wah efforts. The success of Islamic propagation relies on the ability of Muslim communities to engage with the local socio-cultural context, gain support from the government, and foster collaboration with non-Muslim communities. Educated and context-aware local Muslim scholars play a vital role in strengthening Muslim identity and facilitating interfaith dialogue. International funding and networking alleviate local resource constraints, but transparency and accountability in fund management remain essential. Social media platforms have broadened the reach of da'wah, enabling more personalized interactions between preachers and worshippers. Key challenges include government policies, social prejudice, and negative stereotypes. However, collaborative approaches and support from both local and international actors present significant opportunities to enhance Islamic da'wah in the Philippines.